(untitled) (Editora Impacto Científico, 2025)
Payments for Environmental Services (PES) are economic instruments aimed at incentivizing the preservation and sustainable use of natural resources through financial transfers to those who provide environmental services. This study reviews the existing literature on PES, focusing on the role of Environmental Law in promoting sustainability through regulatory frameworks and legal instruments. The analysis identifies the main challenges and opportunities for the effectiveness of PES in Brazil, highlighting the importance of robust legislation, continuous monitoring, and the participation of multiple stakeholders. Examples of successful initiatives, such as the Floresta Mais Amazon Project and the Bolsa Floresta Program, are discussed, emphasizing the need for regulatory improvements and capacity building of those involved. It concludes that, although promising, PES in Brazil still face challenges to consolidate as effective tools for environmental conservation and sustainable development. DOI: https://doi.org/10.56238/edimpacto2025.090-085